Modal Politik Dan Strategi Elektoral Terri Genta Sansui Siregar Pada Pemilu DPRD Kabupaten Tapanuli Utara Tahun 2024 - Tampubolon, Desy Dwi Wulan A; Pasaribu, Ian; Putri, Revi Jeane; Nasuhaidi, Nasuhaidi (Indonesian Democracy Research Center, 2025)
Political capital is a collection of social, symbolic, and relational resources that enable an individual to participate in and influence political processes. This study analyzes the political capital and electoral strategies employed by Terri Genta Sansui Siregar, a young candidate who was successfully elected as a member of the North Tapanuli Regency DPRD in the 2024 elections. Using qualitative research methods, data was collected through observation, interviews, and documentation. The results of the study show that Terri Genta's victory was based on three main elements of her political capital: trust, political legacy, and field activities. Trust was built through a personal approach, dialogue, and direct interaction with the community, including the younger generation. The political legacy of her parents, who had served as members of the DPRD, provided significant advantages in terms of networks and legitimacy. Meanwhile, consistent field activities, such as door-to-door visits and social assistance, strengthened her closeness to constituents. The electoral strategy used included communication and branding, a direct approach, understanding of the terrain, and the utilization of social capital. This victory shows that a combination of strong political capital and relevant campaign strategies is key to gaining public support, especially in local political contests.